STRATEGI PEMASARAN SMARTPHONE OPPO DI KOTA PADANG - Yanti, Budi; Yonaldi, Sepris (LLDIKTI Wilayah X, 2017)
This study aims to determine the effect of four marketing mix variables partially and simultaneously on purchasing decisions Oppo smartphone in Padang. This study uses descriptive quantitative techniques and accidental sampling survey with a sample of 100 respondents. results of the study explains, that is significantly positively Product variables influencing purchase decision variables Smartphone Oppo products in Padang with sig. The resulting 0,000 less than the significance value (0.05), significantly positively influence the variable variable price product purchase decisions Smartphone Oppo in the city of Padang with sig. produced by 0,023 less than the significance value (0.05), that variable does not affect the distribution of the product purchase decision variables Smartphone Oppo in the city of Padang with sig. generated at 0.232 greater than the significance value (0.05), and the variable does not affect the distribution of the product purchase decision variables Smartphone Oppo in the city of Padang with sig. generated at 0, 663 is greater than the significance value (0.05). with sig is 0,000 less than the value of 0.05 that is on the analysis of F test shows that the product strategy, pricing, distribution and prmosi simultaneously own a significant influence on consumer purchasing decisions on Smartphone Oppo in the city of Padang.